Autoinflammatory diseases: An immunologist’s view - A. Yu. Shcherbina (Современная ревматология)
Autoinflammatory syndromes (AISs) are a heterogeneous group of genetically determined diseases, whose basis is the dysregulated mechanisms of inflammation. Despite the fact that traditional primary immunodeficiencies and AISs have an external dissimilarity, there are many parallels, such as hypodiagnosis, multisystem pattern of lesion, chronic inflammation-induced complications, possible medical therapy using cytokine inhibitors, and cardinal cure by stem cell transplantation and gene therapy.There are more than 25 different AISs, their common manifestations are fever episodes accompanied by laboratory inflammatory activity, polymorphous eruption, lymphoproliferative syndrome, and injury to different organs.Genetic analysis plays an important role in the diagnosis in traditional AISs and primary immunodeficiencies. This is particularly relevant to AISs that are not infrequently very closely allied phenotypically. Moreover, it is important that the detection of a causative genetic defect frequently determines man-agement tactics for patients.For AIS treatment, there is a spectrum of agents modulating these or those inflammatory components. However, there is a problem of resistance to standard therapy as before. Pathogenetic therapy for AISs is lifetime, expensive, and commonly responsible for serious adverse reactions, which worsens quality of life in patients. Patients with AISs, like those with other primary immunodeficiencies, need a multidisciplinary approach with the participation of various specialists. These patients should be followed up in specialized centers that perform treatments according to the international algorithms. Since the early diagnosis of primary immunodeficiencies and AISs is a key to their successful treatment; primary care physician’s awareness of these rare diseases is of the most importance.